Anthranilate hydroxylase from Aspergillus niger: new type of NADPH-linked nonheme iron monooxygenase. - Subramanian, V (1984)
Anthranilate hydroxylase from Aspergillus niger catalyzes the oxidative deamination and dihydroxylation of anthranilic acid to 2,3-dihydroxybenzoic acid. This enzyme has been purified to homogeneity and has a molecular weight of 89,000. The enzyme is composed of two subunits of 42,000 with 2 gram-atoms of nonheme iron per mol. Fe2+-chelators like alpha,alpha'-dipyridyl and o-phenanthroline are potent inhibitors of the enzyme activity. Absorption and fluorescence spectra of the enzyme offer no evidence for the presence of other cofactors like flavin. Flavins and flavin-specific inhibitors like atebrin have no effect on the activity of the enzyme. The enzyme incorporates one atom of oxygen each from 18O2 and H218O into the product 2,3-dihydroxybenzoic acid. Based on these studies, it is concluded that anthranilate hydroxylase from A. niger is a new type of NADPH-linked nonheme iron monooxygenase.